Tropospheric Gravity Waves as Observed by the High‐Resolution China Radiosonde Network and Their Potential Sources. Issue 23 (3rd December 2022) - Zhang, Jian; Guo, Jianping; Xue, Haile; Zhang, Shaodong; Huang, Kaiming; Dong, Wenjun; Shao, Jia; Yi, Ming; Zhang, Yehui
Abstract: Lower atmospheric gravity waves (GWs) can significantly impact waves in the middle and upper atmospheres and are vital for turbulence generation. This paper puts the spotlight on the spatial–temporal variability of tropospheric GW total energy ( E T ) and its potential sources above four regions of interest (ROIs) gathered from high‐resolution radiosonde observations from the China Radiosonde Network during the years 2016–2019. The seasonality of E T above four ROIs shows different characteristics and is dependent on latitudes and underlying terrains, reaching its maximum identified in the winter at middle latitudes. Interestingly, the annual cycles of the maximal E T shift from 35°N in October to 25°N in March of the next year, triggered by the shift in the winter subtropical jet. Based on the random forests regressor, the jet stream between 200 and 125 hPa likely serves as the primary source for the observed GWs above the ROIs with low and middle latitudes, with relative contributions of around 60%. However, the Kelvin–Helmholtz instability between 800 and 125 hPa could be the most recognized source of GWs and contributes around 68.4% to the observed energy. During the rainy season, the E T under scenarios of convective precipitation is around 20% larger than the other. As well, as the near‐surface or low‐level wind interacts with a mountain barrier over the Tibetan Plateau region, 12.4% of the observed E T is attributed to the strength of the low‐level wind. Plain Language Summary: The gravity wave (GW) is one of the most important waves in the atmosphere and acts as a triggering source to turbulence. However, the tropospheric GWs in the context of China has seldomly been investigated by using high‐resolution radiosonde data set. This analysis shows that the GW total energy exhibit obvious seasonal various at low and middle latitudes, with maximal identified in the winter and minimal in the summer. The jet stream in the upper troposphere is the most important source for GW at low and middle latitudes and gives rise to a southward propagation of the maximal GW energy in cold season. In the summer of southern China, the convective precipitation could contribute to the enhancement of GW energy. In addition, 12.4% of the observed GW energy is attributed to the strength of the low‐level wind over the Tibetan Plateau. Key Points: Jet stream is the dominant source for gravity waves (GWs) at low and middle latitudes and triggers southward movement of GW energy core during cold seasons Over the Tibetan Plateau, Kelvin–Helmholtz instabilities and terrain‐induced flows contribute to the intensive GW activities During the summertime of southern China, convective precipitation could contribute to the enhancement of energy of about 20%